Improving flow-based market coupling by integrating redispatch potential - Evidence from a large-scale model - Michael Bucksteeg; Simon Voswinkel; Gerald Blumberg (ZBW - Leibniz Information Centre for Economics, 2023)
Power markets have been gradually integrated to achieve the target of a single European market. A major step was the introduction of the flow-based market coupling (FBMC) in Central Western and Eastern Europe (Core region). FBMC reflects the physical constraints of the underlying transmission grid in detail. However, the European Commission and regulators imposed minimum margins to increase cross-border trade and to foster price convergence between the different bidding zones, neglecting physical constraints and increasing redispatch volumes. Integrating redispatch poten-tials into FBMC allows for moving closer to physical reality while maintaining a high level of cross-border trade. In this study, we develop a multi-stage model covering capacity calculation, market coupling, and redispatch stages. This study is the first to evaluate different options for integrating FBMC and redispatch potentials based on a large-scale numerical analysis of Central Europe. The results reveal that minimum margins effectively increase cross-border trade. However, this comes at a high cost due to additional redispatch needs, which reduce overall welfare. Integrating redis-patch potentials in the market-clearing stage leads to a more efficient increase in cross-border ca-pacities and elevates welfare. In the case of combining both approaches, the analysis indicates improved welfare of roughly 80 M exteuro per year.
Keywords: Q4; 330; Flow-based market coupling; European electricity market; cross-border trade; congestion management; redispatch; market modeling